Efficiency with Constructed Wetlands System Using Water Ferns (Azolla microphylla) to Treat Laundry Wastewater - Puspitasari, Nadaa; Suwartha, Nyoman (Syntax Corporation, 2024)
This research aims to analyze the efficiency of processing liquid waste from the laundry industry using the Free Water Surface Constructed Wetland (FWS) system with Azolla microphylla plants. The research method used is experimental research by manipulating independent variables and controlling other relevant variables, as well as observing the effect on the dependent variable. Laundry waste samples were taken from Berkah Laundry, Puri Gading, Bekasi. The results showed that the biomass of Azolla microphylla plants increased significantly from day 0 to day 12, with a growth rate between 0.0289 – 0.0477 grams/day and plant density between 185.19 ind/m2 – 277.78 ind/m2. The influent BOD concentration of laundry liquid waste during the acclimatization stage ranged from 5.89 – 10.54 mg/L, while the effluent BOD ranged from 4.35 – 6.98 mg/L, with the highest efficiency reaching 33.8%. The constructed wetland system with Azolla microphylla plants has proven to be effective in reducing pollutant content in liquid waste, with a BOD removal efficiency of 11.1% - 17.7% and COD of 14.5% - 39%. The conclusion of this research is that the use of artificial wetlands with Azolla microphylla plants can be an effective and environmentally friendly alternative solution for processing liquid waste from the laundry industry. The implications of this research show the potential for applying constructed wetland technology in the clothes washing industry to reduce the negative impact of waste on the environment.